Conceptual framework of minimalism and absolute music composition in “Quarteve” - Bagus Pusaka Lazuardi (Universitas Pendidikan Indonesia, 2023)
Music creation plays a role in the art world that has existed in society for generations against human civilization and is familiar in everyday life. Various forms of expression have an idea from the composer's background and are poured into music, thus creating satisfaction for the creator. Music continues to develop in society, experiencing gradations and reductions in the creative process of its creators. This research uses qualitative research methods because the focus of this creation is how to find the implementation of minimalist music by knowing the elements of music, including its form and structure. Qualitative research intends to understand the phenomenon of what is experienced by the research subject, such as behavior, perception, motivation, action, and others holistically. The conceptual framework is a method used to explain the relationship or relationship between the variables to be studied; in this case, minimalism music as a variable will then be associated with the creation of a musical composition, so it is hoped that the conceptual framework can describe the ideas that will be arranged and designed. The process of making this composition is carried out by researching using several stages, starting with analyzing literature studies. Based on the author's results in creating a composition design, the conceptual framework can be used as a basis for research.